Morphological and Molecular Detection of Hard Ticks in Stray Cats in Mosul city, Iraq. - Nadia Hamid Mohammed; Nadia Sultan Alhayali; Ahmed khalaf Ali (مجلة الانبار للعلوم البيطرية)
The results of the study showed the infestation rate of ticks in stray cats was 52.22% one type of hard tick was diagnosed Rhipicephalus sanguineus it was relied on the macroscopic examination and PCR technique was used for the existing species. The study recorded a high rate of infection in animals of age groups younger than one year with a significant difference depending on age and no significant difference was recorded in the infestation rate between males and female cats. The study also showed the spread of ticks in separate areas of the animal’s body, where it was noted that the highest area of tick presence was in the ear and the back with an infection rate of 80.9% and 68.1%, respectively, while the lowest percentage of ticks was around the perianal and tail with an infection rate was 19.1%. The study also recorded a high rate of infection in the hot months with a significant difference in the percentage of infection depending on the months of the study